Epigene and Hypogene Gypsum Karst Manifestations of the Castile Formation: Eddy County, New Mexico and Culberson County, Texas, USA - Stafford Kevin W.; Nance Raymond; Rosales-Lagarde Laura; Penelope J. Boston (International Journal of Speleology, 2008)
Permian evaporites of the Castile Formation crop out over ~1,800 km2 in the western Delaware Basin (Eddy County, New Mexico and Culberson County, Texas, USA) with abundant and diverse karst manifestations. Epigene karst occurs as well-developed karren on exposed bedrock, while sinkholes dominate the erosional landscape, including both solutional and collapse forms. Sinkhole analyses suggest that more than half of all sinks are the result of upward stoping of subsurface voids, while many solutional sinks are commonly the result of overprinting of collapsed forms. Epigene caves are laterally limited with rapid aperture decreases away from insurgence, with passages developed along fractures and anticline fold axes. Hypogene karst occurs as diverse manifestations, forming the deepest and longest caves within the region as well as abundant zones of brecciation. Hypogene caves exhibit a wide range of morphologies from complex maze and anastomotic patterns to simple, steeply dipping patterns, but all hypogene caves exhibit morphologic features (i.e. risers, outlet cupolas and half-tubes) that provide a definitive suite of evidence of dissolution within a mixed convection (forced and free convection) hydrologic system. Extensive blanket breccias, abundant breccia pipes and numerous occurrences of calcitized evaporites indicate widespread hypogene speleogenesis throughout the entire Castile Formation. Although most cave and karst development within the Castile outcrop region appears to have hypogene origins, epigene processes areactively overprinting features, creating a complex speleogenetic evolution within the Castile Formation.